Android-Integrated Physics Modules with Contextual Inquiry for Students’ Critical Thinking and Digital Literacy - Siti Nurjannah; Syifaul Gummah; Lovy Herayanti; Muhammad Fuaddunnazmi (Department of Physics Education, Universitas Mataram, 2026)
This study aimed to develop an Android-integrated physics learning module based on a contextual inquiry approach to support students’ critical thinking skills and digital literacy at MAN 3 Mataram. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analyze, Design, Development, Implementation, and Evaluation stages. The participants were 17 eleventh-grade students at MAN 3 Mataram. Data were collected through observations, questionnaires, and tests and analyzed using descriptive statistics, N-Gain analysis, and paired-samples t-test. The developed module integrated the Physics Formulas application as a supporting learning medium. Expert validation results showed an average validity score of 84.40%, categorized as very valid. The implementation results indicated a high N-Gain score of 75.48% and a statistically significant difference between pretest and posttest scores, t(16) = 15.54, p < .001. Students’ critical thinking and digital literacy responses reached 92.50% and 87.50%, respectively. Therefore, the developed module was considered feasible and demonstrated potential to support technology-based physics learning.